2017
DOI: 10.7596/taksad.v6i3.899
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Leadership Skills Development Program for University Students / Üniversite Öğrencilerine Yönelik Liderlik Becerileri Geliştirme Programının Etkililiği

Abstract: The aim of this study was to examine the effectiveness of a leadership skills education program for higher education students. In this program, education was provided to improve the desire for struggle and goal setting, communication skills, group skills, problem-solving skills, decision-making skills, responsibility awareness, trusting and trustworthiness awareness, leadership awareness and emotional awareness within the framework of leadership skills. The study group of the research consists of finalyear stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…In addition, it was determined that there was an increase in the sub-dimensions of the Young Leadership Characteristics Scale compared to the first test average of the experimental group. As a result of the research conducted by Cansoy (2017) on university students, it was observed that all levels of students' desire for struggle and goal setting, communication skills, group skills, problem solving skills, decision-making skills, awareness of responsibility, trust and reliability, leadership awareness and emotional awareness increased significantly thanks to their participation in the leadership skills training program. In Cansoy's (2015) study with secondary school students, it was found that students had the highest level of trust and reliability, and the lowest level of communication skills.…”
Section: Dıscussıonmentioning
confidence: 99%
“…In addition, it was determined that there was an increase in the sub-dimensions of the Young Leadership Characteristics Scale compared to the first test average of the experimental group. As a result of the research conducted by Cansoy (2017) on university students, it was observed that all levels of students' desire for struggle and goal setting, communication skills, group skills, problem solving skills, decision-making skills, awareness of responsibility, trust and reliability, leadership awareness and emotional awareness increased significantly thanks to their participation in the leadership skills training program. In Cansoy's (2015) study with secondary school students, it was found that students had the highest level of trust and reliability, and the lowest level of communication skills.…”
Section: Dıscussıonmentioning
confidence: 99%
“…Chapter DOI: https://dx.doi.org/10.46679/isbn978819484832502 individuals to think and using the appropriate tools and strategies in the classroom support the development of leadership skills (Cansoy, 2017;Greenier & Whitehead, 2016).…”
Section: This Chapter Is a Part Of The Book 'Innovations In Educationalmentioning
confidence: 99%